Communication technologies used by nurses in prenatal care - Cavalcante Facundo, Sue Helem Bezerra (2020)
Objective: The study aimed to identify the communication technologies used by prenatal nurses in Primary Health Care. Methods: This descriptive cross-sectional study was conducted with 97 nurses in 27 Primary Health Care Centers of Fortaleza, Ceará, Brazil. Data were collected from July to November 2016 through an author-developed questionnaire addressing sociodemographic issues and educational and communication technologies. Inclusion criteria were prenatal nurses with at least an eight-month experience and three months on the current job. Data were analyzed using the Statistical Package for the Social Sciences, version 20.0. Results: Admission of pregnant women was not performed by 50.5% (49) of the nurses. Most nurses 70.5% (68) did not receive training on technology use and 81.4% (79) used SISPRENATAL. In all, 94.8% (92) of the participants used the electronic medical record and the prenatal record card. Conclusion: The main technologies used for monitoring pregnancy progress were the electronic medical record and the prenatal record card. There is notably a lack of training on technology for nurses.